The legal concept of shared natural resources - Nawrot, Filip (Polish Yearbook of Environmental Law, 2018)
The aim of this study is to define legal issues related to cross-border mining, the so-called shared natural resources, and to present solutions to problems identified accordingly. The first step will involve an analysis of the concept of shared natural resources, which will be conducted in this paper. The first section of the paper provides a theoretical basis needed for further discussion. It presents definitions of natural resources and their classification. The second part of the study presents definitions of shared natural resources established in the legal acts, the doctrine of the law, and proposed by author his own definitions. The relation between the concept of mineral and shared natural resources is presented at the end of this paper.